PELATIHAN PEMBUATAN KONTEN TUR VIRTUAL UNTUK SISWA SMA DI KOTA TANGERANG - Armielia, Adestya Ayu; Prawira, Oqke (Universitas Pelita Harapan, 2022)
The direct impact of Covid-19 pandemic is the occurrence of large-scale social restriction globally. This affects all industrial sectors to transform digitally, and obviously the negative impact on the tourism sector is felt because of its intangible nature. To make it worse, this condition has been going on for too long. The limited social activities and movement also affect psychological problems. Travel consumers are turning to virtual travel agencies’ interactive communications that have emerged as a result of the digital transformation in tourism sector. The innovation of virtual tours with virtual reality development in tourism 4.0 are able to restore tourism activities in pandemic and positively help the psychological problems from the tourism consumers. In addition, virtual tourism can be carried out by anyone, not only by tourism agency. Public or community can also optimize this activity to help promoting the tourist destinations in their area, especially for students in high schools who want to work in digital marketing in the future. Therefore, training on creating the virtual tour content and virtual tour activities are implemented. The methods used include literature studies, questionnaires, and interviews for preparation of the materials and evaluation of the activities. For the training, presentation and lecture methods, as well as practicum are also implemented. The result of the activity showed that the comprehension and digital skills of the participants are improved, and mentally, they enjoyed the event. Other results include virtual trip module and videos which are also used in classroom learning materials.